Fracture mechanics : fundamentals and applications - Anderson, T. L. 1957- (CRC Press/Taylor & Francis Group, 2017)
Fracture Mechanics: Fundamentals and Applications, Fourth Edition is the most useful and comprehensive guide to fracture mechanics available. It has been adopted by more than 150 universities worldwide and used by thousands of engineers and researchers. This new edition reflects the latest research, industry practices, applications, and computational analysis and modeling. It encompasses theory and applications, linear and nonlinear fracture mechanics, solid mechanics, and materials science with a unified, balanced, and in-depth approach. Numerous chapter problems have been added or revised, and additional resources are available for those teaching college courses or training sessions. Dr. Anderson's own website can be accessed at www.FractureMechanics.com.
Keywords: Fracture mechanics.; elektronické knihy; electronic books